Rynek skarbowych papierów wartościowych w Stanach Zjednoczonych - Wójtowicz, Zbigniew (Treasury Securities Market in the United States, 2005)
In this paper the market of the treasury securities issued by the Treasury Department of the United States and federal agencies is presented as well as ways of their issu and structure and value of the market of the treasury securities on the background of the entire market of the debt securities in the United States. The difference in the characteristics of the individual types of the treasury securities causes that this became a market for both institutional as well individual investors with varying lengths of periods of investing. The market of the treasury securities is the third one, as regards its value, after the markets of mortgage backed securities and corporate bonds. The market of the treasury securities, because of its liquidity and position of the issuer, remains in the centre of interest of both the domestic as well as foreign investors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 78-93